Ділянка “Декоративні форми” - Vakulenko, T.B.; Klimenko, A.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The results of introduction plants and the reconstruc tion of the plot "Ornamental forms" in M.M. Gryshko National Botanical Gardens are given. The collection composition is analysed. The most perspective for landscape design cultivars are found.